Hematemesis as Initial Presentation in a 10-Week-Old Infant with Eosinophilic Gastroenteritis - Varun Shetty; Kayla E. Daniel; Anil Kesavan (Hindawi Limited, 2017)
Eosinophilic gastroenteritis is a rare condition characterized by eosinophilic inflammation in the gastrointestinal tract resulting in a variety of gastrointestinal symptoms. There is currently a dearth of information on this topic in the pediatric literature, as very few cases have been reported. In this report, we present a case of eosinophilic gastroenteritis in a 10-week-old patient with initial presenting symptom of hematemesis. To our knowledge, this is the youngest case reported in the literature and is unique in its initial presentation.